2021
DOI: 10.3390/molecules27010129
|View full text |Cite|
|
Sign up to set email alerts
|

Dexamethasone Attenuates Oncostatin M Production via Suppressing of PI3K/Akt/NF-κB Signaling in Neutrophil-like Differentiated HL-60 Cells

Abstract: Oncostatin M (OSM) plays a role in various inflammatory reactions, and neutrophils are the main source of OSM in pulmonary diseases. However, there is no evidence showing the mechanism of OSM production in neutrophils. While dexamethasone (Dex) has been known to exert anti-inflammatory activity in various fields, the precise mechanisms of OSM downregulation by Dex in neutrophils remain to be determined. Here, we examined how OSM is produced in neutrophil-like differentiated HL-60 cells. Enzyme-linked immunosor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 58 publications
(82 reference statements)
0
3
0
Order By: Relevance
“…During oxidative stress, in the nucleus, Nrf2 is released from the Keap1-Nrf2 complex. A number of studies have shown that activating the PI3K/AKT signaling pathway can facilitate nuclear translocation of Nrf2 [9,19,20]. Inflammation and induced Ox-LDL may be prevented by activating HO-1 and modulating it.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During oxidative stress, in the nucleus, Nrf2 is released from the Keap1-Nrf2 complex. A number of studies have shown that activating the PI3K/AKT signaling pathway can facilitate nuclear translocation of Nrf2 [9,19,20]. Inflammation and induced Ox-LDL may be prevented by activating HO-1 and modulating it.…”
Section: Introductionmentioning
confidence: 99%
“…The cytoprotective enzyme HO-1 controls inflam have shown that activating Nrf2 can boost HO-1 act working, HO-1 expression is inhibited, and oxidative pressor, Keap1, Nrf2 is inactive in the cytoplasm unde oxidative stress, in the nucleus, Nrf2 is released from th of studies have shown that activating the PI3K/AKT s clear translocation of Nrf2 [9,19,20]. Inflammation and i by activating HO-1 and modulating it.…”
Section: Introductionmentioning
confidence: 99%
“…In the original article [ 1 ], there was a mistake in Figure 1 as published. The authors want to change the time in Figure 1b from 15 min, 30 min, 45 min, 1 h, 2 h, 3 h, and 4 h to 5 min, 10 min, 15 min, 30 min, 1 h, 2 h, and 3 h. The corrected Figure 1 appears below.…”
mentioning
confidence: 99%